Quality of Life Outcomes after endoscopic sinus surgery: Chronic Rhinosinusitis with and without nasal polyps - Martins Pereira, Sara (2017)
Objectives: To determine the quality of life improvement of chronic rhinosinusitis (with or without polyps) patients who underwent endoscopic sinus surgery.Study Design: Retrospective.Material and Methods: We analyzed the the SNOT-22 questionnaire responses of patients who underwent endoscopic sinus surgery between January 2013 and April 2015 in Hospital de Braga, comparing before and after surgery.Results: We obtained a total of 189 patients with a mean age of 44.88 years. The chronic rhinosinusitis with polyps group (CRSwNP) amounted to 48.15%. The average time between surgery and the questionnaire response was 20.11 months. The CRSwNP group had an average score SNOT-22 preoperative of 50 and 15 after surgery, while the chonic rhinosinusitis without polyps group (CRSsNP) had a mean preoperative score of 39 and postoperative 21.Conclusion: The endoscopic sinus surgery has a significant impact on quality of life improvement for chronic rhinosinusitis patients.